Penerapan Sertifikasi Rainforest Alliance di Unit Kebun Malabar PT Perkebunan Nusantara VIII Pangalengan - Fadhilah, Adistia; Yudha, Eka Purna (Universitas Galuh, 2025)
Rainforest Alliance certification assists numerous farmers and companies worldwide to ensure social, environmental, and economic sustainability in consumer production processes. The Malabar Plantation Unit of PT Perkebunan Nusantara VIII made a significant decision by implementing Rainforest Alliance certification in 2009. This study identifies the background of the implementation and process. It evaluates the impact of Rainforest Alliance certification on the plantation's operations, productivity, and tea prices at the Malabar Plantation Unit. The research method used is descriptive analysis, employing farm performance analysis and a case study approach. Data were obtained through in-depth interviews with plantation management, environmental surveys around the plantation, production activity surveys, and related document analysis. The research results indicate that the implementation of certification has brought positive changes, particularly regarding employee welfare and the surrounding environment, although there are still some aspects that do not fully meet the implementation requirements. Additionally, the certification has enhanced the production, productivity, and price of orthodox tea at the Malabar Plantation Unit. This study concludes that although the certification implementation process presents some challenges, it can provide long-term benefits for environmental sustainability and plantation welfare.